INTERREGINAL RAILWAY TRANSPORT IN CZECH REPUBLIC (Perner's Contacts, 2010)
The paper deals with railway transport among regions in Czech Republic and it is focused on Pardubicky region. In this region correlation between number of departure and region characteristics is calculated,
Keywords: railway transport; Pardubicky region; correlation analysis